Formulation of wound healing hydrogel based on keratin derived from chicken feather - Priyaah, Kumaran (2014)
A novel cross-linked keratin hydrogel dressing was developed by incorporating keratin from chicken feather into hydrogel dressing formulation. Keratin fibers from feathers are non-abrasive, eco-friendly, biodegradable, insoluble in organic solvents and also have good mechanical properties, low density, hydrophobic behaviour and finally low cost. In the matter of fact, keratinocytes (epidermal cells that manufacture and contain keratin) migrate from wound edges to cover the wound during healing process. These characteristics open a new approach to do research on keratin based hydrogel which derived from chicken feather for wound care product. In this study, the physical properties of keratin based hydrogel and its wound healing efficacy on small wounds in rabbits were assessed. Keratin based hydrogels have been done for five types of formulation. Optimum concentration of keratin has been identified from previous studies. Some of analysis of keratin based hydrogel includes spectroscopic analysis using Fourier transform infrared and Raman, microbial count analysis and heavy metal test using Inductively Coupled Plasma Mass Spectrometer (ICP-MS). XRD analysis was performed to analyse the crystallinity index of the hydrogel which lied between 30-50% of crystallinity. Morphological details are observed with optical, transmission and scanning electron microscopy. Swelling and solubility tests are carried out on the hydrogel to observe the solid content and water absorbance capacity of the hydrogel. Application of keratin hydrogel dressings significantly enhanced (P < 0.05) wound closure and accelerated the rate of re-epithelialization as compared to control hydrogel and other film dressing. Overall, this product is safe to use and acted as an effective wound healing product with appropriate hydrogel characteristics. Thus, the studies reviewed can be the scaffolding to increase the use of this protein for wound care product as the keratin from chicken feathers are shown as a novel eco-friendly material which is very beneficial and profitable.